Character Establishment Through Literacy Movement In Elementary School - Ika Ratnaningrum; M. Jazuli; Tri Joko R; Widodo Widodo (Universitas Negeri Semarang, 2023)
As an effort to achieve the nation's goals, namely to educate and advance people's lives, especially in the field of education, the government started the School Literacy Movement (GLS) activities in accordance with the Regulation of the Minister of Education and Culture Number 23 of 2015 concerning the Growth of Character. Literacy is an integral aspect of the world of education. School Literacy Activities are one of the development programs that are expected to also develop students' literacy skills, interest in reading and writing skills. Literacy skills are strongly influenced by students' reading and writing skills. The purpose of the GLS is in accordance with the latest guidebook, namely to grow and strengthen the character of students through cultivating the school literacy ecosystem so that students become lifelong learners. The meaning of this statement is that the purpose of GLS is not only limited to cultivating students' habits in reading, writing, and improving students' abilities in mastering knowledge and literacy skills. The purpose of GLS is interpreted to be able to grow and strengthen student character. This is because habituation, development and learning activities are continuous and continuous activities, so that positive habits that are carried out during the implementation of the GLS can foster positive character in students.